Penerapan Metode ARAS Pada Pendukung Keputusan Penerimaan Karyawan dengan Pembobotan ROC - Riadi, Rizka Salsabila (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
A retail company adopts the concept of a hybrid convenience store, combining a minimarket and a cafe. The company's recruitment process for prospective employees is still manual and inefficient in making decisions to recruit employees who meet the company's criteria. Employees are the most important thing in a company for the company to thrive in the era of globalization. Based on the problems described above, a Decision Support System (DSS) is needed to help overcome these problems. By implementing the Rank Order Centroid (ROC) method, which can provide weighted values for each existing criterion based on its priority level. And to rank it using the Additive Ratio Assessment (ARAS) method, which can provide decision-making based on the highest ranking or value, it is hoped that this can help the company in making decisions regarding employee recruitment selection. So that the employee recruitment selection process can be more efficient. The results of this study indicate that a decision support system (DSS) built using the ARAS method and ROC weighting can assess prospective employees, with Alternative A4 achieving the highest final score of 0.9036.